Booster dose of COVID-19 mRNA vaccine does not increase risks of myocarditis and pericarditis compared with primary vaccination: New insights from the vaccine adverse event reporting system - Chen, Congqin; Fu, Fang; Ding, Lingqing; Fang, Jie; Xiao, Jie (Frontiers in Immunology, 2022)
Background: Despite the likely association between coronavirus 2019 (COVID-19) mRNA vaccines and cases of myocarditis/pericarditis, the benefit–risk assessment by the Centers for Disease Control (CDC) still showed a favorable balance for the primary series of COVID-19 mRNA vaccinations. Since August 2021, a full-scale booster vaccination in certain recipients has been recommended. Great concerns about whether the COVID-19 mRNA booster vaccination could increase the risks of myocarditis/pericarditis have been raised since then. The present study aimed to compare the incidence rates and risks of myocarditis/pericarditis between booster and primary vaccination programs. Methods: The CDC COVID Data Tracker and the Vaccines Adverse Event Reporting System (VAERS) were queried between December 11, 2020 and March 15, 2022. Incidence rates were calculated by cases of myocarditis/pericarditis divided by the number of vaccinated people or the total doses of COVID-19 mRNA vaccines. Disproportionality patterns for myocarditis/pericarditis of different COVID-19 mRNA vaccinations were accessed based on the reporting odds and proportional reporting ratios (ROR and PRR, respectively). Results: A total of 2,588 reports of myocarditis/pericarditis were identified after administration of primary-series COVID-19 mRNA vaccination and 269 after the booster dose program during the study period. The incidence of myocarditis/pericarditis following booster COVID-19 mRNA vaccination was lower than that of primary series. The results showed significantly high reporting of myocarditis/pericarditis following the administration of primary COVID-19 mRNA vaccination, whereas the disproportional level was lower in the booster-dose vaccination. Conclusion: This study found that the booster dose of COVID-19 mRNA vaccination when compared with primary series course did not lead to an increase in the risks of myocarditis/pericarditis.